2018
DOI: 10.3390/s18113932
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Transformer Winding Temperature and Strain Detection Based on Distributed Optical Fibre Sensors

Abstract: The temperature distribution and deformation of the transformer windings cannot be measured in a distributed manner by the traditional method and failure location cannot be performed. To solve these problems, we present a transformer winding temperature and strain based on a distributed optical fibre sensing detection method. The design of the optical fibre winding composite model is developed and simulated winding temperature rise test and local deformation test distinguish between measuring the winding tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Liu et al [16] designed a scheme for grooved winding with a sensing fiber in it, then using ROTDR and BOTDR to detect the winding deformation. However, the design of the slotted wire has greatly changed the structure of the wire, which has reduced its ampacity and short-circuit resisting ability, and it is difficult to extract the fiber in the actual production process of the transformer.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [16] designed a scheme for grooved winding with a sensing fiber in it, then using ROTDR and BOTDR to detect the winding deformation. However, the design of the slotted wire has greatly changed the structure of the wire, which has reduced its ampacity and short-circuit resisting ability, and it is difficult to extract the fiber in the actual production process of the transformer.…”
Section: Introductionmentioning
confidence: 99%
“…A liquid-core sensing fibre, usually a glass tube (the cladding) filled with an ultra-transparent liquid of high refractive index, is commonly used to generate bigger change in η(z). (b) BS-based fibre temperature sensor [154][155][156][157][158]: The temperature perturbations affect the refractive index of the sensing fibre, thus changing the Brillouin frequency shift ν B , according to the equation [159]:…”
Section: Ss-based Fibre Temperature Sensormentioning
confidence: 99%
“…The equation indicates that BS-based fibre sensor can also be used to detect distributed strain along the sensing fibre. (c) RS-based fibre temperature sensor [160][161][162][163][164]: Since Anti-Stokes RS is much more sensitive to temperature than Stokes RS, the ratio of Anti-Stokes and Stokes Raman-scattered light intensities provides valuable information on temperature perturbations, according to the equation [159]:…”
Section: Ss-based Fibre Temperature Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of elastic scattered light is the same as the frequency of the incident light, whereas the frequency of inelastic scattered light is offset from the frequency of the incident light. The study found that the scattering of light in the fibre includes Rayleigh scattering, Brillouin scattering and Raman scattering (Figure 1) [22]. Rayleigh scattering is elastic, whereas Brillouin scattering and Raman scattering are inelastic.…”
Section: Detection Principlementioning
confidence: 99%